Sociology as an Experimental Science of Non-logical Actions. The Relevance of Pareto’s Work Today - Riccioni, Ilaria (Italian Sociological Review, 2024)
Over the past few years, in terms of a theoretical approach to reality, sociology seems to be lagging behind in disclosing the meanings and dynamics of social issues in connection with individuals’ problems (Mills, 1965). Society has changed dramatically, and the classic sociological tools appear wholly inadequate for the new social reality. And we can also thank postmodernist theories for this, since they managed to deconstruct a number of sociological tools without providing satisfactory alternatives. In the case of Vilfredo Pareto, by the beginning of the 19th century he had already realized that economics was not enough to explain social issues but despite this was becoming the dominant discipline used to tackle social demands. The purpose of this article is to examine those aspects of the work of Pareto that are still relevant for thinking about the current social reality and, in particular, about the potential tools that this work can still offer us today, if properly explored.